2001
DOI: 10.1007/s004310100805
|View full text |Cite
|
Sign up to set email alerts
|

Serological rebound in congenital toxoplasmosis: long-term follow-up of 133 children

Abstract: serological rebound is common in children with congenital toxoplasmosis but, due to the risk and constraints, an additional course of treatment and more ophthalmological surveillance than currently practiced do not seem warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 9 publications
3
32
0
3
Order By: Relevance
“…4, IgG titers paralleled IFN-␥ levels. This antibody profile (i.e., transitory negation followed by rebound) is commonly observed for treated patients (14,24). The impact of treatment in reducing the IFN-␥-specific response in tuberculosis has been described previously (1,9,15) and suggests that such tests could be used for monitoring patient response to treatment (1).…”
Section: Discussionmentioning
confidence: 74%
“…4, IgG titers paralleled IFN-␥ levels. This antibody profile (i.e., transitory negation followed by rebound) is commonly observed for treated patients (14,24). The impact of treatment in reducing the IFN-␥-specific response in tuberculosis has been described previously (1,9,15) and suggests that such tests could be used for monitoring patient response to treatment (1).…”
Section: Discussionmentioning
confidence: 74%
“…Only IgE is commonly related to bad clinical prognosis, and IgG4 could have either negative or no influence. 7,22,100,101 The few studies on the role of anti-T. gondii antibodies on congenital infections indicate that fetuses or newborns who produce specific IgG2, IgG4 or IgE have bad clinical prognosis. 7,22,100,101…”
Section: Igs and Fcrs Polymorphismsmentioning
confidence: 99%
“…Our study revealed 22 congenitally infected infants with IgG seronegativity in the Liaison (Table 1) and seropositivity in the Sabin-Feldman dye test. Furthermore, in subsequent samples the infants were seropositive, but this was not a serological rebound but rather a lack of sensitivity (3,35). In particular, a diminished sensitivity of the Liaison IgG was observed between 6 and 12 months of life due to the decrease of maternally diaplacental antibodies against Toxoplasma gondii.…”
Section: Discussionmentioning
confidence: 91%